2012
DOI: 10.1007/s00259-012-2211-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of primary tumour FDG uptake with clinical, histopathological and molecular characteristics in breast cancer patients scheduled for neoadjuvant chemotherapy

Abstract: Primary tumour FDG uptake in breast cancer patients scheduled for neoadjuvant chemotherapy is significantly higher in tumours with prognostically unfavourable characteristics. Based on tumour characteristics associated with low tumour FDG uptake, this study was unable to identify a subgroup of patients unlikely to benefit from pretreatment PET/CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 38 publications
7
62
2
1
Order By: Relevance
“…Explanation of exclusion reasons, b e.g., reviews, editorials, guidelines, and perspectives; c e.g., optical imaging and scintimammography; Table 1. Characteristics of studies reporting on mammography, breast ultrasound, MRI, and (17,18,70,87,91,(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107). Of these, eight articles reported on two imaging modalities: five on both breast ultrasound and mammography (28,33,41,52,56), and three on both 18 F-FDG PET and DWI (70,87), or MRS (91).…”
Section: Resultsmentioning
confidence: 99%
“…Explanation of exclusion reasons, b e.g., reviews, editorials, guidelines, and perspectives; c e.g., optical imaging and scintimammography; Table 1. Characteristics of studies reporting on mammography, breast ultrasound, MRI, and (17,18,70,87,91,(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107). Of these, eight articles reported on two imaging modalities: five on both breast ultrasound and mammography (28,33,41,52,56), and three on both 18 F-FDG PET and DWI (70,87), or MRS (91).…”
Section: Resultsmentioning
confidence: 99%
“…Evreleme amaçlı yapılan PET incelemede görülen lenf nodu sayısına göre lenfatik bölge RT planlamasının irdelendiği devam eden çalışmaları mevcut. Özellikle neoadjuvan kemoterapi planlanan hastalarda, tedavi yanıtının değerlendirilmesinde ve tahmin edilmesinde histopatolojik subtipler ile MR ve PET-BT'nin karşılaştı-rıldığı çok sayıda devam eden çalışma dikkat çekiyor (30)(31)(32)(33).…”
Section: Güncel Yaklaşımdan Dikkat çEkici öRneklemelerunclassified
“…Buck [24], Avril [29], and Bos [30] confirmed that in invasive ductal carcinomas the Ki-67 LI is higher than in the lobular type tumors. Shimoda et al [31], Gil-Rendo et al [32] and Koolen et al [33] found significant correlation between Ki-67 LI and the SUV max , as well as between the mitotic count and the FDG-uptake. Tchou et al reported that triple negative breast cancer displays higher Ki-67 expression, grade and mitotic count than other histological subtypes and their FDG-uptake is also significantly higher [34].…”
Section: *Decrease In the Percent Of The Baseline (Pretherapy) Suv Mamentioning
confidence: 99%